2010
DOI: 10.1038/jhg.2010.116
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the SHOC2 gene in Noonan-like syndrome and in hematologic malignancies

Abstract: Noonan syndrome is an autosomal dominant disease characterized by dysmorphic features, webbed neck, cardiac anomalies, short stature and cryptorchidism. It shows phenotypic overlap with Costello syndrome and cardio-facio-cutaneous (CFC) syndrome. Noonan syndrome and related disorders are caused by germline mutations in genes encoding molecules in the RAS/MAPK pathway. Recently, a gain-of-function mutation in SHOC2, p.S2G, has been identified as causative for a type of Noonan-like syndrome characterized by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 27 publications
5
37
1
3
Order By: Relevance
“…Intriguingly, some of these subjects were reported to have features suggestive of Costello syndrome, especially in early infancy. More recently, a number of reports confirmed the distinctive phenotype associated with the c.4A > G mutation, but also provided evidence for a wider clinical variability characterizing this disorder [Komatsuzaki et al, 2010;Digilio et al, 2011;Lee et al, 2011;Capalbo et al, 2012;Hoban et al, 2012;Gripp et al, 2013;Ş imşek-Kiper et al, 2013;Gargano et al, 2014;Zmolikova et al, 2014]. Table I summarizes the main clinical features of the SHOC2 cases reported in literature.…”
Section: Discussionmentioning
confidence: 72%
“…Intriguingly, some of these subjects were reported to have features suggestive of Costello syndrome, especially in early infancy. More recently, a number of reports confirmed the distinctive phenotype associated with the c.4A > G mutation, but also provided evidence for a wider clinical variability characterizing this disorder [Komatsuzaki et al, 2010;Digilio et al, 2011;Lee et al, 2011;Capalbo et al, 2012;Hoban et al, 2012;Gripp et al, 2013;Ş imşek-Kiper et al, 2013;Gargano et al, 2014;Zmolikova et al, 2014]. Table I summarizes the main clinical features of the SHOC2 cases reported in literature.…”
Section: Discussionmentioning
confidence: 72%
“…20 In two of the initial studies on this disorder, cardiac defects have been observed in 27 out of 33 (~80%) individuals. 20,59 Compared with individuals with NS, septal defects (~42%) and mitral valve anomalies (~31%) were more frequent. 20,59 In following case reports on individuals with the SHOC2 p.S2G mutation, phenotypic variability was noted.…”
Section: Rasa1mentioning
confidence: 99%
“…The abnormally high concentration of SHOC2 now available to membrane-bound Ras translates into heightened ERK activity, an event believed to belie NS/LAH pathogenesis. Characterized by a range of cognitive and skeletal abnormalities, patients with NS/LAH also present with a number of cardiac and dermatological conditions, in many ways resembling those identified with genetic disorders stemming from mutant desmosomal proteins (93)(94)(95). NS/LAH symptoms like hyperkeratosis and abnormalities of palm and sole skin, in particular, are reminiscent of features associated with SPPK.…”
Section: Figurementioning
confidence: 99%